Optimized Sustainable Off-Online-Hybrid Channels of Recycling Unwanted Vehicles by Reutilising Forward Sale Networks - Miao, Junhong; Jiang, Zilu; Wan, Zhong (International Journal of Industrial Engineering: Theory, Applications and Practice, 2025)
In line with continuously improved living standards, the amount of unwanted vehicles (UWVs) is increasing as the consumption of vehicles is being rapidly upgraded. This research aims to design a strategic UWV recycle system with resource-conservation and environmentally-friendly advantages. A nonlinear bi-level programming model is first constructed to optimize cooperation strategies between the manufacturer (leader) and the auto 4S shops (followers), including repurchasing prices and processing ways for distinct types of UWVs, the provided convenience and incentive policies to UWV-holders. Then, an efficient smoothing algorithm is developed to solve this complicated model in virtue of model reformulation and its property analysis. Numerical simulation is employed to reveal their practical implications. Main findings include: Reusing of existing vehicle sales network not only can reduce transportation cost, but also greatly improves sustainability of the UWV recycle system; Differential strategy of processing the UWVs with different damage-aging degrees can greatly improve their utilization rate and the total system profit; Governmental subsidy and differences of user groups both play critical roles in facilitating cooperation of recycle enterprises and efficiency of this system. It is seen that, unlike existing results, this study provides an off-online-hybrid-channel strategy for recycling the UWVs with the synergism of manufacturers and auto 4S shops in the decision-making framework of the Stackelberg game. The optimal strategies can be provided by the developed new model and algorithm, and the values of this research are further validated by numerical simulation.